Exploring Students’ Experiences of Task-Based Language Teaching (TBLT) in Vocabulary Learning: A Narrative Inquiry - Windi Melia Putri (Journal of Languages and Language Teaching, 2022)
Task-based language teaching (TBLT) is a learning method that is considered more comprehensive compared to the communicative method, which has been considered far more useful in language teaching. TBLT proposes the use of tasks as a main component in the language classroom because it provides better context for learners to activate their acquisition process and promote second language learning. The current research compares the growth of students' vocabulary knowledge in English. This study aims to know the students’ experiences of TBLT in vocabulary learning. The qualitative research method used in this study is a narrative inquiry. Data was collected through semi-structured interviews based on interview guidelines and data analysis by involving students in the online learning process. The findings provide information about the learning process as well as the advantages of TBLT in vocabulary learning. The interview results show that students, in general, have a positive attitude toward learning vocabulary through TBLT method. It can be concluded that there are various positive experiences explained by participant, such as the use of TBLT in vocabulary learning is more interesting in learning process and students can master more new vocabulary when using the TBLT method.